Perawatan Topikal Intensif Gingivitis Deskuamasi Oral Lichen Planus pada Pasien Hipertensi - Liza Meutia Sari; Harum Sasanti (Faculty of Dentistry, Universitas Indonesia, 2015)
Oral lichen planus (OLP) is a chronic inflammatory condition that affects the oral mucous membranes with a variety of clinical presentations, including reticular, atrophic (desquamative gingivitis) and ulcerative lesions.Treatment aims primarily to reduce the length and severity of symptomatic outbreaks. We report a case of OLP in 53 years old female patient with hypertension as underlying disease. The patient had been treated with nifedipine and reserpine for twelve years. Management of the patient included the application of 0.05% clobetasol propionate in a custom tray for erosive gingival lesions, nutritional supplementation, oral hygiene promotion and cosultation to internal medicine specialist. The improvement of oral lesions progressed well within six months. We conclude that the successful treatment of OLP requires a complete assessment of the medical status and elimination of local exacerbating factors. Systemic drug therapy is needed if OLP is suspected as the cause of oral lichenoid lesions. Changing to other drug regimes may also become necessary for improved immune status.